NTC thermistor composition and thermistor element

By using a specific composition of NTC thermistor composition in the NTC thermistor element, the problem of large resistance change rate in the laminated NTC thermistor element during characteristics changes before and after installation and high temperature and high humidity environment is solved, and the effects of excellent thermal stability and small deviation of resistance value are achieved.

CN120072434APending Publication Date: 2025-05-30TDK CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411450781.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-11-28
Filing Date
2024-10-17
Publication Date
2025-05-30

AI Technical Summary

Technical Problem

The characteristics of the existing stacked NTC thermistor elements have greatly changed before and after installation, and the resistance change rate is large in high temperature and high humidity environments, which affects the reliability of the equipment.

Method used

A specific composition of NTC thermistor composition is used, wherein the total Mn, Co, and Ni is set to be 100 mol%, the Mn content is 40 to 63 mol%, the Co content is 10 to 30 mol%, the Ni content is 15 to 35 mol%, the Al content is 5.9 mol%, and it is preferable that Fe or Cu is not included to improve thermal stability and reduce the deviation of resistance value.

Benefits of technology

It achieves excellent thermal stability relative to heat during reflow treatment, small deviation of resistance value, and good reliability in high temperature and high humidity environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120072434A_ABST
    Figure CN120072434A_ABST
Patent Text Reader

Abstract

The invention provides an NTC thermistor composition which can realize an NTC thermistor element with excellent thermal stability relative to heat during reflow treatment and small deviation of resistance value, and a thermistor element with the composition. The NTC thermistor composition comprises 40 to 63 mol% of Mn, 10 to 30 mol% of Co, 15 to 35 mol% of Ni, and less than 5.9 mol% of Al (including 0).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an NTC thermistor composition and a thermistor element having a thermistor layer composed of the composition. Background Art

[0002] An NTC (negative temperature coefficient) thermistor element has a characteristic that its resistance value decreases as the temperature rises, and is used for various applications such as temperature sensors or temperature compensation elements in various devices such as electronic devices. Since the devices in which such thermistor elements are installed can be used in various environments, high reliability is required for the thermistor elements. Specifically, a thermistor element with a small resistance change rate even in a high-temperature and high-humidity atmosphere of 120°C or higher is required. For example, a thermistor element having the composition shown in Patent Document 1 below is being developed.

[0003] The thermistor element having the composition shown in Patent Document 1 is preferably a thermistor composition used in, for example, a glass diode type thermistor, a glass bead type thermistor, or a resin bead type thermistor.

[0004] Prior Art Documents

[0005] Patent Documents

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2009-188179 Summary of the Invention

[0007] Technical Problem to be Solved by the Invention

[0008] Recently, although a stacked chip type thermistor element has also been developed, the present inventors have found that in a stacked type thermistor element, the characteristics change significantly depending on the composition before and after mounting the thermistor element on a circuit board or the like of various electronic devices.

[0009] In view of such actual circumstances, the present invention has been completed, and an object thereof is to provide an NTC thermistor composition capable of achieving excellent thermal stability with respect to heat during reflow processing and having a small deviation in resistance value, and a thermistor element having the composition.

[0010] Means for Solving the Technical Problem

[0011] In order to achieve the above object, one aspect of the present invention provides an NTC thermistor composition, wherein

[0012] when the total of Mn, Co, Ni, and Al is set to 100 mol%, it contains:

[0013] 40 to 63 mol% of Mn,

[0014] 10 to 30 mol% of Co, and

[0015] 15 to 35 mol% of Ni, and

[0016] Al is 5.9 mol% or less (including 0).

[0017] As a result of the inventors' dedicated investigation of the NTC thermistor composition, it was found that by including Mn, Co, and Ni within a specified range, an NTC thermistor element with excellent thermal stability with respect to heat during reflow processing and a small deviation in resistance value can be achieved, until the completion of the present invention.

[0018] It may also contain 0 to 2.5 mol% of Zr.

[0019] Preferably, it contains more Ni than Co. By configuring it in this way, the thermal stability is improved, and the deviation of the resistance value is further reduced.

[0020] Preferably, it substantially does not contain Fe or Cu. If either is substantially contained in the composition, there is a tendency for the thermal stability to decrease and a tendency for the deviation of the resistance value to increase. In addition, substantially not containing means that it can be contained within a range that does not significantly impede the thermal stability and does not significantly increase the deviation of the resistance value. For example, it may contain 0.5 mol% or less of Fe or Cu in the composition.

[0021] Preferably, the composition has spinel-type metal oxide particles with an average particle size of 10 μm or less. By configuring it in this way, there are the following advantages: the density of the composition is increased, the thermal stability is further improved, the deviation of the resistance value is further reduced, and the firing temperature can be lowered, so it is easy to control the shrinkage of the internal electrode and the resistance value deviation can be reduced.

[0022] The NTC thermistor element according to one aspect of the present invention has the NTC thermistor composition described in any one of the above. According to this NTC thermistor element, when the element is mounted on a circuit board or the like, even after multiple reflow processes, the change in characteristics is small, the thermal stability is excellent, and the deviation of the resistance value is also small.

[0023] Preferably, the size of the element is 0.6 mm or less in the first axis direction and 0.3 mm or less in the second axis direction. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a schematic cross-sectional view of an NTC thermistor element according to an embodiment of the present invention.

[0025] Figure 2It is a graph showing the resistance change rates of the elements in the embodiments and comparative examples of the present invention.

[0026] Symbol Explanation

[0027] 1... NTC thermistor element; 2... Element body; 2a... Thermistor layer; 2b... Protective layer; 3... Internal electrode layer; 3a... First internal electrode layer; 3a1... Discontinuous portion; 3b... Second internal electrode layer; 3b1... Discontinuous portion; 4... External electrode. Detailed Embodiment

[0028] Hereinafter, the embodiments will be described with reference to the drawings. In the figures, the X-axis, Y-axis, and Z-axis are perpendicular to each other.

[0029] Thermistor Element

[0030] As Figure 1 shown, the NTC thermistor element 1 of the present embodiment has an element body 2 and external electrodes 4, 4 provided at both ends of the element body 2 in the X-axis direction. Inside the element body 2, internal electrode layers 3 are laminated at a predetermined interval along the Z-axis direction with the thermistor layer 2a sandwiched therebetween, and protective layers 2b are laminated outside the internal electrode layers located on the outermost side along the Z-axis.

[0031] The internal electrode layer 3 has a pair of first internal electrode layers 3a with a first predetermined pattern and a second internal electrode 3b with a second predetermined pattern located therebetween, both of which are continuous along the Y-axis according to Figure 1 the pattern shown, and are discontinuous along the X-axis in a part. The first internal electrode layer 3a is formed with a discontinuous portion 3a1 at a substantially central portion along the X-axis in such a way as to cut off the electrical conduction between the first internal electrode layers 3a located on both sides. The first internal electrode layers 3a located on both sides of the discontinuous portion 3a1 along the X-axis are respectively connected to the separated external electrodes 4, 4. At the discontinuous portion 3a1, the thermistor layer 2a and the protective layer 2b are continuous.

[0032] The second internal electrode layer 3b located between the pair of first internal electrode layers 3a, 3a along the Z-axis is formed with a pair of discontinuous portions 3b1 at positions respectively close to the external electrodes 4, 4 along the X-axis in such a way as to cut off the electrical conduction between the second internal electrode layer 3b with an isolated pattern located at the substantially center and either of the external electrodes 4, 4. At the discontinuous portion 3b1, the two thermistor layers 2a are continuous.

[0033] The width of the second internal electrode layer 3b of the isolated pattern located at the center along the X-axis is greater than the width of the intermittent portion 3a1 of the first internal electrode layer 3a along the X-axis. Moreover, when viewed from the direction along the Z-axis, the second internal electrode layer 3b of the isolated pattern located at the center along the X-axis repeats with the first internal electrode layers 3a located on both sides along the X-axis, and the portion of the thermistor layer 2a located in the repeated portion becomes the active layer of the thermistor layer. In addition, the number of stacked layers or the pattern shape of the internal electrode layers 3a and 3b is not limited to Figure 1 the example shown. As long as it is the number of layers or the pattern shape for forming the thermistor circuit, there is no particular limitation.

[0034] In the present embodiment, the thermistor layer 2a and the protective layer 2b are preferably composed of a thermistor composition of the same material. However, since the protective layer 2b hardly affects the characteristics of the thermistor element, it may also be composed of an insulating material composition different from the thermistor layer 2a. In the present embodiment, the thermistor layer 2a is composed of an NTC thermistor composition described later.

[0035] The first internal electrode layer 3a and the second internal electrode layer 3b preferably contain a noble metal element as a conductive component. The noble metal element contained in the internal electrode is not particularly limited, and may contain one or more elements selected from Pd, Ag, and Pt. In addition to the above noble metal elements, the internal electrode layers 3a and 3b may also contain base metal elements such as Ni and Cu as conductive components.

[0036] The external electrode 4 preferably contains a noble metal element as a conductive component. The noble metal element contained in the external electrode 4 is not particularly limited, and may contain one or more elements selected from Pd, Ag, and Pt. In addition to the above noble metal elements, the external electrode 4 may also contain base metal elements such as Ni and Cu as conductive components. In addition to the above metal elements, the external electrode 4 may also contain a glass component. The glass component is added to promote the sintering of the external electrode 4 and to impart mechanical strength to the external electrode. The composition of the external electrode 4 is not particularly limited. For example, it may contain 60% by volume or more and 95% by volume or less of a metal component and 5% by volume or more and 40% by volume or less of a glass component. The composition of the glass component contained in the external electrode is not particularly limited and may be appropriately set according to the intended use. The glass component contained in the external electrode may contain, for example, at least one selected from alkaline earth metals, Cu, Si, Ti, Zn, alkali metals, Sr, Al, and Bi.

[0037] The size of the NTC thermistor element 1 of the present embodiment is not particularly limited, but preferably, it is 0.6 mm or less along the X-axis direction, 0.3 mm or less along the Y-axis, and 0.3 mm or less along the Z-axis. In addition, the thickness of the thermistor layer 2a is not particularly limited, and is preferably 5 to 100 μm.

[0038] In the present embodiment, the thermistor layer 2a is composed of an NTC thermistor composition, and preferably has spinel-type metal oxide particles having an average particle diameter of 10 μm or less, and these particles are arranged in the thermistor layer 2a at a predetermined density. By setting the particle diameter of the oxide particles to 10 μm or less, the sintered body density increases and the thermal stability becomes high. In addition, as a control method for setting the particle diameter of the oxide particles to 10 μm or less, there is no particular limitation. For example, it is sufficient to classify the ceramic slurry by sieving.

[0039] Whether the thermistor layer 2a has spinel-type metal oxide particles can be determined, for example, by analyzing the thermistor layer 2a using X-ray diffraction. In addition, the average particle diameter of the metal oxide particles can be obtained, for example, by observing the cross section of the thermistor layer 2a using a scanning electron microscope and averaging 100 or more particles. In addition, by observing the cross section of the thermistor layer 2a using the same method, the density of the metal oxide can also be analyzed, for example, the number ratio of particles per 100 square μm. In the thermistor layer 2a, in addition to the metal oxide particles, segregation particles or the like may be present, but preferably it is 5% or less in terms of the area ratio of the cross section.

[0040] In the present embodiment, as the metals contained in the NTC thermistor composition constituting the thermistor layer 2a, at least Mn, Co, and Ni are included, and Al and Zr may be included as needed. Preferably, Fe or Cu is substantially not included.

[0041] In the present embodiment, when the total of Mn, Co, Ni, and Al is set to 100 mol%, the content of Mn is 40 to 63 mol%, preferably 47 to 60 mol%. By setting the content of Mn within a predetermined range, the resistance change rate becomes smaller and the resistance value variation coefficient also becomes smaller. As the reason, it is considered that if the content of Mn is too small, there is a tendency that self-heating becomes more and it is difficult to use as an NTC thermistor element, and if it is too much, there is a tendency that the structural stability decreases and the thermal stability becomes low.

[0042] In addition, the resistance change rate represents the change rate of the resistance of the NTC thermistor element having the NTC thermistor composition of the present embodiment before and after passing through the reflow furnace several times. In terms of the resistance value variation coefficient, a plurality of NTC thermistor elements having the NTC thermistor composition of the present embodiment are prepared, and the deviation between individuals of their resistance values at 25°C is represented. The smaller the coefficient, the smaller the deviation between individuals.

[0043] The content of Co is 10 to 30 mol%, preferably 13 to 25 mol%, and more preferably 15 to 23 mol%. By setting the content of Co within a specified range, the resistance change rate also becomes smaller, and the resistance value variation coefficient also becomes smaller. As the reason, it is considered that if the content of Co is too small, there is a tendency for the structural stability to decrease and the thermal stability to become low, and if it is too much, there is a tendency for it not to be solid-soluted and to be easily precipitated as a heterogeneous phase, and there is a tendency for the resistance value deviation to increase.

[0044] In addition, the content of Ni is 15 to 35 mol%, preferably 17 to 31 mol%, and more preferably 21 to 27 mol%. By setting the content of Ni within a specified range, the resistance change rate also becomes smaller, and the resistance value variation coefficient also becomes smaller. As the reason, it is considered that if the content of Ni is too small, there is a tendency for the structural stability to decrease and the thermal stability to become low, and if it is too much, there is a tendency for it not to be solid-soluted and to be easily precipitated as a heterogeneous phase, and there is a tendency for the resistance value deviation to increase.

[0045] Regarding Al, it may not be contained in the composition, but it may also be contained. In the case of containing it, it is 5.9 mol% or less. By setting the content of Al within a specified range, the resistance change rate also becomes smaller, and the resistance value variation coefficient also becomes smaller. As the reason, it is considered that if the content of Al is too much, there is a tendency for it not to be solid-soluted and to be precipitated as a heterogeneous phase, and the deviation of the resistance value increases. In addition, compared with the case where Al is not contained, by containing Al, it is advantageous in that there is a tendency for the structural stability to increase and the thermal stability to become high. In this regard, the content of Al is preferably 1.9 to 4.8 mol%.

[0046] Preferably, the content of Ni is more than the content of Co. By configuring in this way, the resistance change rate also becomes smaller, and the resistance value variation coefficient also becomes smaller. As the reason, it is considered that the valence change becomes smaller and the thermal stability is improved. In addition, by making the content of Ni more than the content of Co, a reduction in manufacturing cost can be expected.

[0047] Regarding Zr, it may not be contained in the composition, but it may also be contained. In the case of containing it, it is 2.5 mol% or less. By setting the content of Zr within a specified range, the resistance change rate also becomes smaller, and the resistance value variation coefficient also becomes smaller. As the reason, it is considered that the valence change becomes smaller and the thermal stability is improved.

[0048] Preferably, Fe is substantially not contained in the NTC thermistor composition of the present embodiment. By substantially not containing Fe, both the resistance change rate and the coefficient of variation of the resistance value become smaller. The reason for this is that when Fe is substantially contained, the deviation of the resistance value becomes larger. In addition, "substantially not contained" means that Fe may be contained as long as it does not hinder the inherent characteristics of the NTC thermistor composition of the present embodiment, and it may be contained as long as it is about 0.5 mol% or less.

[0049] Preferably, Cu is substantially not contained in the NTC thermistor composition of the present embodiment. By substantially not containing Cu, both the resistance change rate and the coefficient of variation of the resistance value become smaller. The reason for this is that when Cu is substantially contained, there is a tendency for the deviation of the resistance value to increase. In addition, "substantially not contained" means that Cu may be contained as long as it does not hinder the inherent characteristics of the NTC thermistor composition of the present embodiment, and it may be contained as long as it is about 0.5 mol% or less.

[0050] In the NTC thermistor composition of the present embodiment, as other metal components, metals such as Ba, Ca, Mo, Nb, Sn, Ti, V, W, and Y may be contained as long as they are about 0.5 mol% or less. Other metals may be contained as long as they do not hinder the inherent characteristics of the NTC thermistor composition of the present embodiment.

[0051] Since the thermistor layer 2a of the thermistor element 1 of the present embodiment is composed of the above-described composition, even if the element 1 is miniaturized, it has excellent thermal stability with respect to heat during reflow processing, and the deviation of the resistance value is small. As the heat during reflow processing, for example, a temperature of 200 °C or higher is considered, and as the number of times of reflow processing applied to the element 1, for example, two or more times are considered. In addition, the thickness W of the thermistor layer 2a is not particularly limited, but is preferably 5 to 100 μm. By setting it within this range, in particular, the deviation of the resistance becomes smaller and the thermal stability is improved.

[0052] The thermistor element 1 of the present embodiment is formed, for example, by applying a conductive paste (outer electrode paste) containing Pd particles to both end faces of an element body 2 made of a ceramic green body and performing a baking process. The element body 2 can be manufactured by the following operations: preparing ceramic pastes that respectively constitute the thermistor layer 2a and the protective layer 2b, and preparing electrode pastes that constitute the internal electrode layers 3a and 3b, laminating the pastes layer by layer by a printing method or the like, drying them, and performing sintering and the like.

[0053] Specifically, the thermistor element 1 is manufactured as follows.

[0054] First, prepare the raw materials of the metals contained in the metal oxide particles of the thermistor composition. In the present embodiment, as the raw materials, prepare manganese oxide, nickel oxide, cobalt oxide, aluminum oxide, zirconium oxide, or raw materials that become these oxides after roasting. As the compounds that become oxides after roasting, for example, carbonates, halogen compounds, oxalates, nitrates, hydroxides, organometallic compounds, etc. containing these metals can be cited.

[0055] Next, weigh the above raw materials and mix them to prepare a mixed powder. As the mixing method, there is no particular limitation. For example, it can be carried out by dry mixing, or water or an organic solvent, etc. can be added to the mixed powder, and using a ball mill, etc., it can be carried out by wet mixing.

[0056] Next, granulate the prepared mixed powder. Granulation is carried out to make the mixed powder into agglomerated particles of an appropriate size and transform it into a form suitable for molding. As the granulation method, for example, a pressure granulation method or a spray drying method, etc. can be cited. The spray drying method is a method of adding a commonly used binder such as polyvinyl alcohol to the mixed powder, atomizing it in a spray dryer, and drying it. The average particle size of the mixed powder (raw material of the thermistor composition) as particles is preferably 50 μm or less.

[0057] Then, add water and a dispersant to the obtained particles and mix them with a ball mill, and further add a binder resin to obtain a ceramic slurry. The ceramic slurry is formed by a doctor blade method to obtain a green sheet with a thickness of about 5 to 100 μm.

[0058] Prepare an internal electrode paste by mixing a noble metal powder and an organic carrier. The average particle size of the noble metal powder is preferably 0.1 μm or more and 5.0 μm or less. The internal electrode paste preferably contains a powder of a noble metal in a specified weight percentage and an organic carrier in a specified weight percentage. The organic carrier can be prepared, for example, by dissolving ethyl cellulose in terpineol.

[0059] Print the internal electrode paste on the green sheet in a specified shape to form an internal electrode pattern. Stack the green sheet with the internal electrode pattern formed and the green sheet without the internal electrode pattern formed in a specified order for a specified number of sheets, and apply pressure to obtain a mother laminate. Cut the mother laminate to a specified size to obtain a sheet-like laminate.

[0060] Next, or in parallel with the above process, prepare an external electrode paste by kneading Pd powder, a frit, and an organic carrier. As the Pd powder, a mixture of spherical Pd powder and flat Pd powder can also be used. As the frit, for example, a frit containing B can be used. The transition temperature of the frit is preferably 400 °C or more and 650 °C or less, and the softening temperature is preferably 500 °C or more and 750 °C or less.

[0061] An organic carrier can be prepared, for example, by dissolving an acrylic resin in terpineol. The content of the acrylic resin in the organic carrier can also be, for example, 5% by weight or more and 40% by weight or less.

[0062] An external electrode paste is coated on one end face and the other end face of the element body 2 as a sintered body in a prescribed shape. The coated external electrode can be dried. The coating thickness of the external electrode paste can be appropriately set according to the thickness of the external electrode set as the target.

[0063] A firing treatment is performed on the external electrode paste coated on one end face and the other end face of the ceramic green body to form a first external electrode 4 provided on one end face and a second external electrode 4 provided on the other end face.

[0064] If necessary, a plating layer can be formed on the surface of the external electrode 4 by electrolytic plating. The plating layer has a function of improving solder wettability or heat resistance during mounting. The composition of the plating layer can be appropriately selected according to the composition of the external electrode, etc. For example, a Ni plating layer can also be formed on the surface of the external electrode 4, and a Sn plating layer can be formed thereon.

[0065] Furthermore, the present invention is not limited to the above-described embodiments, and various changes can be made within the scope of the present invention.

[0066] For example, the NTC thermistor composition of the above-described embodiment is preferably used as the thermistor layer 2a of a laminated chip-type thermistor element, but can also be used as a composition for other types of thermistor elements. As other types of elements, the NTC thermistor composition of the above-described embodiment can be used for, for example, NTC thermistor elements such as glass diode-type thermistors, glass bead-type thermistors, and resin bead-type thermistors.

[0067] Examples

[0068] Hereinafter, the present invention will be described based on more detailed examples, but the present invention is not limited to these examples.

[0069] Examples 1 to 6

[0070] First, as starting materials, commercially available manganese tetroxide (Mn 3 O 4 ), nickel oxide, cobalt oxide, and alumina were weighed and prepared so that the composition after firing became the composition ratio shown in Table 1. Among them, in Table 1, in terms of mol% of Mn, Ni, Co, and Al, the total of Mn, Ni, Co, and Al was set to 100 mol%. These raw materials were blended and wet-mixed in a ball mill for 16 hours. In addition, about 0.1% by weight or less of unavoidable impurities may be included in these starting raw materials.

[0071] Next, the starting materials after wet mixing are dehydrated and dried, and made into a powder using a mortar and pestle. Then, the obtained powder is placed in an alumina crucible and calcined at 800 to 1200 °C for 2 hours.

[0072] Next, the obtained calcined powder is finely pulverized by a ball mill, then dehydrated and dried to form granules of the composition raw material for the thermistor. Water and a dispersant are added to the obtained granules and mixed by a ball mill, and then a binder resin is added to obtain a ceramic slurry. The ceramic slurry is formed by the doctor blade method to obtain a green sheet with a specified thickness.

[0073] An internal electrode paste is prepared by mixing Pd powder, which is a noble metal powder, and an organic carrier. The average particle size of the noble metal powder is 0.5 μm. The internal electrode paste is formed by dispersing the noble metal powder in the organic carrier. The organic carrier is prepared by dissolving ethyl cellulose in terpineol.

[0074] The internal electrode paste is printed on the green sheet in a specified shape to form an internal electrode pattern. The green sheets with the internal electrode pattern formed thereon and the green sheets without the internal electrode pattern formed thereon are stacked in a specified order for a specified number of sheets and pressed to obtain a mother laminate. The mother laminate is cut to a specified size to obtain a sheet-like laminate.

[0075] Next, or in parallel with the above process, an external electrode paste is prepared by kneading Pd powder, frit, and an organic carrier. As the Pd powder, a mixture of spherical Pd powder and flat Pd powder is used. As the frit, for example, a frit containing B is used. The transition temperature of the frit is 520 °C, and the softening temperature is 580 °C.

[0076] The organic carrier is prepared, for example, by dissolving an acrylic resin in terpineol. The content of the acrylic resin in the organic carrier is 30% by weight.

[0077] The external electrode paste is coated on one end face and the other end face of the element body 2, which is a sintered body, in a specified shape. The coated external electrode is dried. The external electrode paste coated on one end face and the other end face of the ceramic green body is subjected to a baking treatment to form a first external electrode 4 provided on one end face and a second external electrode 4 provided on the other end face. A Ni plating layer is formed on the surface of the external electrode 4 by electrolytic plating, and a Sn plating layer is formed thereon. Thus, a sample of the NTC thermistor element 1 is manufactured.

[0078] The evaluation shown in Table 1 was carried out on each sample. Regarding the resistance change rate, the process of putting the sample of the NTC thermistor element 1 into a reflow furnace at a temperature of 260°C for about 10 minutes and then cooling it was repeated six times, and the change rate of the resistance value of the sample after six reflow treatments was expressed relative to the resistance value of the sample before being put into the reflow furnace. The symbol A for the resistance change rate in Table 1 indicates that the change rate of the resistance value of the sample after six reflow treatments is within ±0.5% relative to the resistance value of the sample before the first time being put into the reflow furnace.

[0079] In addition, regarding the coefficient of variation of the resistance value, 30 samples of each NTC thermistor element of Examples 1 to 6 were prepared respectively, the deviation (CV value) between individuals of their resistance values at 25°C was measured, and it was compared with the CV value of Example 1 to investigate the degree of change. The symbol F indicates that the CV value increased by 2.0 or more compared with Example 1, the symbol A indicates that the CV value is 1.4 or more and less than 2.0, the symbol A2 indicates that the CV value is 1.1 or more and less than 1.4, and the symbol A3 indicates that the CV value is less than 1.1.

[0080] In addition, in the determination, the case where the resistance change rate is A and the coefficient of variation of the resistance value is A3 is judged as A3 for marking, the case where the resistance change rate is A and the coefficient of variation of the resistance value is A2 is judged as A2 for marking, the case where the resistance change rate is A and the coefficient of variation of the resistance value is A is judged as A for marking, and the case where the resistance change rate is F or the coefficient of variation of the resistance value is F is judged as F for marking.

[0081] The results of these are shown in Table 1. In addition, regarding the thermistor layer of the sample of element 1 of Examples 1 to 6, cross-sectional photographs were taken using a scanning electron microscope, and the particles were analyzed by X-ray diffraction method, and it was confirmed that these particles are spinel-type oxide particles. In addition, the average particle size of the particles was found to be 10 μm or less.

[0082] Comparative Example 1

[0083] Except that the starting materials were prepared in such a way that the Al content was 7.3 mol% exceeding 5.9 mol% as shown in Table 1, the samples of the element were produced in the same manner as in Example 1, and the same tests and evaluations as in Example 1 were carried out. The results are shown in Table 1.

[0084] Evaluation 1

[0085] As shown in Table 1, compared with the samples of Comparative Example 1 in which the Al content exceeds 5.9 mol%, it was confirmed that good results of both the resistance change rate and the coefficient of variation of the resistance value were obtained in Examples 1 to 6.

[0086] Table 1

[0087]

[0088] Examples 7 to 12, Comparative Examples 2 and 3

[0089] Starting materials were prepared in such a manner that the Al content was set to 2.6 mol% as shown in Table 2, the Mn content was varied in the range of 36.5 to 66.1 mol%, and the Co and Ni contents were changed accordingly. Other than this, samples of the element were fabricated in the same manner as in Example 3, and the same tests and evaluations as in Example 3 were conducted. The results are shown in Table 2.

[0090] Evaluation 2

[0091] As shown in Table 2, compared with the samples of Comparative Examples 2 and 3 in which the Mn content deviated from the range of 40 to 63 mol%, it was confirmed that in Examples 7 to 12 where the Mn content was in the range of 40 to 63 mol%, good results were obtained for both the resistance change rate and the coefficient of variation of the resistance value. In addition, it was confirmed that in Examples 9 to 11 where the Mn content was in the range of 47 to 60 mol%, even better results were obtained for the coefficient of variation of the resistance value.

[0092] Table 2

[0093]

[0094] Examples 13 to 18, Comparative Examples 4 and 5

[0095] Starting materials were prepared in such a manner that the Al content was set to 4.9 mol% as shown in Table 3, the Ni content was varied in the range of 12.0 to 39.0 mol%, and the Mn and Co contents were changed accordingly. Other than this, samples of the element were fabricated in the same manner as in Example 5, and the same tests and evaluations as in Example 5 were conducted. The results are shown in Table 3.

[0096] Evaluation 3

[0097] As shown in Table 3, compared with the samples of Comparative Examples 4 and 5 in which the Ni content deviated from the range of 15 to 35 mol%, it was confirmed that in Examples 13 to 18 where the Ni content was in the range of 15 to 35 mol%, good results were obtained for both the resistance change rate and the coefficient of variation of the resistance value. In addition, it was confirmed that in Examples 14 to 17 where the Ni content was in the range of 17 to 31 mol%, even better results were obtained for the coefficient of variation of the resistance value. It was also confirmed that in Examples 15 to 16 where the Ni content was in the range of 21 to 27 mol%, even better results were obtained for the coefficient of variation of the resistance value.

[0098] Table 3

[0099]

[0100] Examples 19 to 25, Comparative Examples 6 and 7

[0101] Starting materials were prepared such that the content of Al was set to 3.7 mol% as shown in Table 4, the content of Co was varied in the range of 8.1 to 32.3 mol%, and the contents of Mn and Ni were changed accordingly. Other than that, samples of the element were produced in the same manner as in Example 4, and the same tests and evaluations as in Example 4 were carried out. The results are shown in Table 4.

[0102] Evaluation 4

[0103] As shown in Table 4, compared with the samples of Comparative Examples 6 and 7 in which the content of Co deviated from the range of 10 to 30 mol%, it was confirmed that in Examples 19 to 25 where the content of Co was in the range of 10 to 30 mol%, good results were obtained for both the resistance change rate and the coefficient of variation of the resistance value. In addition, it was confirmed that in Examples 20 to 23 where the content of Co was in the range of 13 to 25 mol%, better results were obtained for the coefficient of variation of the resistance value. It was also confirmed that in Examples 4 and 21 to 22 where the content of Co was in the range of 15 to 23 mol%, better results were obtained for the coefficient of variation of the resistance value.

[0104] In addition, as shown in Tables 1 to 4, compared with the examples where the content of Ni was less than the content of Co, it was confirmed that the coefficient of variation of the resistance value was better in the examples where the content of Ni was greater than the content of Co.

[0105] Table 4

[0106]

[0107] Examples 2a to 2b and 6a to 6b

[0108] Starting materials were prepared such that the content of Al was varied as shown in Table 5 and Fe or Cu was included. Other than that, samples of the element were produced in the same manner as in Example 2 or 6, and the same tests and evaluations as in Example 2 or 6 were carried out. The results are shown in Table 5.

[0109] Evaluation 5

[0110] As shown in Table 5, it was confirmed that when Fe or Cu was included, the coefficient of variation of the resistance value deteriorated compared with the case where Fe or Cu was not included.

[0111] Table 5

[0112]

[0113] Comparative Examples 8 to 9

[0114] Except for changing the contents of Mn, Co, Ni, and Al as shown in Table 6 and preparing the starting materials in a manner that does not contain or contains Fe and Cu, samples of the element were fabricated in the same manner as in Example 3, and the same tests and evaluations as in Example 3 were performed. The results are shown in Table 6.

[0115] Evaluation 6

[0116] As shown in Table 6, it was confirmed that when Co was not included, regardless of whether Fe and Cu were included or not, the resistance change rate deteriorated and the coefficient of variation of the resistance value deteriorated. In addition, Figure 2 shows a graph representing the relationship between the number of furnace passes and the resistance change rate in the samples of Comparative Examples 8 and 9. Additionally, Figure 2 shows a graph representing the relationship between the number of furnace passes and the resistance change rate in the samples of Example 3.

[0117] Table 6

[0118]

[0119] Examples 26 to 29

[0120] Except for changing the content of Al as shown in Table 7 and preparing the starting materials by including Zr instead, samples of the element were fabricated in the same manner as in Example 3, and the same tests and evaluations as in Example 3 were performed. The results are shown in Table 7.

[0121] Evaluation 7

[0122] As shown in Table 7, when Zr was included, compared with the case where Zr was not included, it was confirmed that the coefficient of variation of the resistance value was the same, and Zr could also be added up to 2.5 mol%.

[0123] Table 7

[0124]

Claims

1. An NTC thermistor composition, wherein: When the total amount of Mn, Co, Ni and Al is 100 mol %, the following is contained: 40 to 63 mol % of Mn, 10-30 mol% Co, and 15-35 mol% Ni, Al is 5.9 mol% or less, and contains 0.

2. The NTC thermistor composition according to claim 1, wherein: Contains 0 to 2.5 mol% Zr.

3. The NTC thermistor composition according to claim 1, wherein: Contains more Ni than Co.

4. The NTC thermistor composition according to claim 1, wherein: It contains substantially no Fe or Cu.

5. The NTC thermistor composition according to claim 1, wherein: The present invention relates to spinel metal oxide particles having an average particle size of 10 μm or less.

6. An NTC thermistor element, wherein: An NTC thermistor composition according to any one of claims 1 to 5.

7. The NTC thermistor element according to claim 6, wherein: The thickness is 0.6 mm or less in the first axial direction and 0.3 mm or less in the second axial direction.

Citation Information

Patent Citations

  • Composition for thermistor

    JP2009188179A